Regulation of Deubiquitinating Enzymes by Post-Translational Modifications - Das, Tanuza; Shin, Sang Chul; Song, Eun Joo; Kim, Eunice EunKyeong (MDPI, 2020)
Ubiquitination and deubiquitination play a critical role in all aspects of cellular processes, and the enzymes involved are tightly regulated by multiple factors including posttranslational modifications like most other proteins. Dysfunction or misregulation of these enzymes could have dramatic physiological consequences, sometimes leading to diseases. Therefore, it is important to have a clear understanding of these regulatory processes. Here, we have reviewed the posttranslational modifications of deubiquitinating enzymes and their consequences on the catalytic activity, stability, abundance, localization, and interaction with the partner proteins.
Keywords: TUMOR-SUPPRESSOR; UBIQUITIN DYNAMICS; PROTEIN STABILITY; DOWN-REGULATION; PHOSPHORYLATION; ACTIVATION; USP4; LOCALIZATION; SUMOYLATION; MECHANISMS